ENHANCING EDUCATIONAL EFFECTIVENESS IN NIGERIA THROUGH TEACHER’S PROFESSIONAL DEVELOPMENT - Oluremi, Olaleye Florence (European Scientific Journal, ESJ, 2013)
This paper examined teachers professional development and its effect in enhancing educational effectiveness in Osun State, Nigeria. It was a descriptive research design of the survey type. The research was carried out in Osun State Nigeria. 550 teachers were randomly selected from all primary school teachers in the state. Questionnaire tagged self-development questionnaire (SDQ) was used to elicit information from the randomly selected respondents. Data were collected and analysed using percentages and frequency count. Results showed that some programmes were organized for teachers professional development. Some of the programmes were, inservice-programmes such as Sandwich, Distant learning, Workshop, Conferences, Seminars and Orientation programmes. Findings showed that teachers participated in Sandwich programmes to develop themselves professionally and academically. They also participated in National Teachers Institute (NTI) Distant learning programmes to enhance their teaching performance. It was found that the programmes had enhanced and improved their skills in teaching. However, it was found that newly recruited teachers were not properly oriented. Hence it was recommended that teachers should be allowed and encouraged by the school administrators to attend conferences, workshop and seminars regularly.